2020
DOI: 10.1039/c9ew00696f
|View full text |Cite
|
Sign up to set email alerts
|

A new concept in constructed wetlands: assessment of aerobic electroconductive biofilters

Abstract: The METland® concept constitutes a hybrid concept for treating wastewater where microbial electrochemical technologies (MET) are integrated with constructed wetlands (CW) to enhance pollutant removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 67 publications
(74 reference statements)
1
14
0
Order By: Relevance
“…Precisely, the mixed aerobic-anaerobic nature of D1 removed 90% BOD 5 , while the purely aerobic D2 unit removed 94% of BOD 5 regarding the raw WW. The results were consistent with data obtained in previous studies of METland R configurations (Prado et al, 2019;Ramírez-Vargas et al, 2019), including those reported by Aguirre-Sierra et al (2020) with COD removal ranging from 82 to 99% in vertical down-flow configuration. The differences were possibly related with the higher oxygen availability due to the passive aeration of the downflow (D2) configuration.…”
Section: Effectiveness Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…Precisely, the mixed aerobic-anaerobic nature of D1 removed 90% BOD 5 , while the purely aerobic D2 unit removed 94% of BOD 5 regarding the raw WW. The results were consistent with data obtained in previous studies of METland R configurations (Prado et al, 2019;Ramírez-Vargas et al, 2019), including those reported by Aguirre-Sierra et al (2020) with COD removal ranging from 82 to 99% in vertical down-flow configuration. The differences were possibly related with the higher oxygen availability due to the passive aeration of the downflow (D2) configuration.…”
Section: Effectiveness Analysissupporting
confidence: 92%
“…Thus, METland R is a term to denominate such general concept and it does not imply any specific operation mode. So, such systems can be operated either under flooded and anoxic mode (Aguirre-Sierra et al, 2016) or under downflow aerobic one (Aguirre-Sierra et al, 2020). Interestingly, bacteria from Geobacter genus were abundant as part of the electroactive biofilm regardless of the operation, anaerobic or aerobic (Aguirre-Sierra et al, 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy, these wastewaters contained organic matter, while the system tested here was fully autotrophic. For instance, microbial electrochemical wetlands reached values below 15 gN·m −3 ·d −1 ( Aguirre-Sierra et al, 2020 , Xu et al, 2017 ). When a constructed wetland was coupled with a denitrifying MET, a maximum total nitrogen removal rate of 76 gN·m −3 ·d −1 was observed ( He et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…( Sleutels et al, 2012 ). However, the development of MET-based treatment concepts such as snorkels ( Hoareau et al, 2019 , Viggi et al, 2015 ) or METlands ( Aguirre-Sierra et al, 2020 , Prado et al, 2020 ) highlights the importance of the microbial ecology function over reactor materials and engineering ( Koch et al, 2018 ). In consequence, only two components might be needed to reach an improvement of bioremediation activities: the appropriate microbiome inhering electroactive microorganisms and a conductive support serving as electrode.…”
Section: Introductionmentioning
confidence: 99%
“…The electron flow along the METland bed was demonstrated by measuring the profile of electric potential along long distances [ 13 , 14 ]. Although most of the MET-based applications are classically operated under anoxic conditions to avoid oxygen competition with anodic reactions, METland has been recently proved to be effective even under down-flow aerated mode [ 15 , 16 ] where nitrification reactions are favored. Full scale METland units have been already constructed at 0.4 m 2 per person equivalent and demonstrated to be sustainable according to a recent Life Cycle Analysis [ 16 ] using different electroconductive granular material like electroconductive coke [ 17 ] or more sustainable materials like electroconductive biochar (ec-biochar) obtained after wood pyrolysis at high temperature [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%